2013
DOI: 10.2319/062813-481.1
|View full text |Cite
|
Sign up to set email alerts
|

Influence of active reminders on oral hygiene compliance in orthodontic patients

Abstract: A text message reminder system is effective for improving oral hygiene compliance in orthodontic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
126
1
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(158 citation statements)
references
References 26 publications
7
126
1
8
Order By: Relevance
“…Since numerous studies have shown that sending mobile text-messages as prompt cues is an effective way to improve oral hygiene during fixed orthodontic treatment [43,51,52], the app also provides an option for setting reminders for oral health-behavior tasks and the use of the brushing-timer.…”
Section: The User Has 3 Fluoride Moments Per Daymentioning
confidence: 99%
See 2 more Smart Citations
“…Since numerous studies have shown that sending mobile text-messages as prompt cues is an effective way to improve oral hygiene during fixed orthodontic treatment [43,51,52], the app also provides an option for setting reminders for oral health-behavior tasks and the use of the brushing-timer.…”
Section: The User Has 3 Fluoride Moments Per Daymentioning
confidence: 99%
“…To establish oral health-behavior change (targeting determinants: "support" and "cues to action/habit formation"), practical support and prompt cues were identified as useful methods [34,43,51,52]. To provide practical support, the app incorporates a brushing-timer, which users can turn on when they decide to brush.…”
Section: The User Has 3 Fluoride Moments Per Daymentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that there is an initial decline in oral hygiene after bonding followed by increase in oral hygiene after 5th month of orthodontic treatment. 1 There are increased chances of WSLs around orthodontic brackets with excessive plaque accumulation. Inadequate plaque controls either pretreatment or during orthodontic treatment is associated with increased chances of WSL.…”
Section: Introductionmentioning
confidence: 99%
“…2 Earlier studies have shown that oral hygiene can be improved with reward system or active reminder therapy. 1 A systematic review in 2009 demonstrated the influence of text messages on behavioral changes in 13 out of 14 studies. 4 Nowadays, mobile usage has increased dramatically.…”
Section: Introductionmentioning
confidence: 99%